Enhancing hybrid learning through effective facilities management in remote settings - Maisyaroh, Maisyaroh; Juharyanto, Juharyanto; Wiyono, Bambang Budi; Adha, Maulana Amirul; Ansar, Rudy; Ariyanti, Nova Syafira (Journal of Education and Learning (EduLearn), 2025)
In the unpredictable digital age, it is imperative to guarantee the availability and use of learning facilities to maximize the success of hybrid-based learning, particularly for schools located in remote places. This research aims to find in-depth information about the management of learning facilities in assisting remote areas hybrid-based learning success. This study used a qualitative approach and a case study design. While in-depth interview and documentation studies were used in data collection, the study was conducted in three schools in remote areas with participants in this study including principals, teachers, students, and parents. The data obtained were also checked for credibility and data validity. The findings showed that the learning facilities management (LFM) in encouraging the successful application of hybrid learning in schools located in remote areas, showed the adequacy of the management of adequate facilities, but not on the management of facilities at home with some specificities found. This limitation is caused by economic and geographical factors, where many families in remote areas cannot afford the necessary learning devices or do not have stable internet access. This study has contributed to the literature on management of learning facilities in the post-pandemic period which can form the basis for further research in related fields.